Enhanced Low‐Frequency Monopole and Dipole Acoustic Antennas Based on a Subwavelength Bianisotropic Structure. Issue 4 (29th January 2020) - Jia, Yurou; Luo, Yanchun; Wu, Dajian; Wei, Qi; Liu, Xiaojun
Abstract: High‐efficiency sound emission is crucial in practical scenarios, such as sonar system and acoustic communication. However, the efficient emission of the low‐frequency sound source is difficult because of the large acoustic radiation reactance from the ambient medium. Here, a subwavelength bianisotropic hybrid Mie resonator (BHMR) is proposed, which has shown excellent capability in converting a central monopole source into the enhanced monopole and dipole acoustic antennas at low frequency. The simulated acoustic field distributions and far‐field radiations of the BHMR demonstrate that the enhanced omnidirectional and directional antennas are induced by the monopole and dipole resonances, respectively. A BHMR sample is further fabricated and the enhancements of the monopole and dipole acoustic antennas by the BHMR are experimentally verified. The miniature BHMR offers an alternative way to achieve the enhanced low‐frequency monopole and dipole antennas that are highly desirable for loudspeaker design and acoustic communication. Abstract : A subwavelength bianisotropic hybrid Mie resonator (BHMR) is presented to convert a central monopole source into both enhanced monopole and dipole acoustic antennas at low frequency. The enhancements of monopole and dipole emissions are verified numerically and experimentally. This miniature BHMR enabled low‐frequency enhanced omnidirectional and directional sound antennas are highly desirable for loudspeaker design and acoustic communication.